2017
DOI: 10.1055/s-0036-1588559
|View full text |Cite
|
Sign up to set email alerts
|

Triarylmethyl Cation Catalysis: A Tunable Lewis Acid Organo­catalyst for the Synthesis of Bisindolylmethanes

Abstract: Triarylmethyl cations serve as tunable organocatalysts for the synthesis of bisindolylmethanes. The catalyst structure can be modified to increase or decrease reactivity as needed to match the requirements of the substrate. High yields are achieved for a variety of substrates by using these green catalysts. Catalyst tuning allows for the use of less reactive electrophiles by increasing the reactivity of the catalyst. Acid-sensitive products can be isolated under these mild reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Recently we reported that trityl cations are exceptional catalysts for the synthesis of bisindolylmethanes via aldehyde activation (Figure 1), and the tunability of these catalysts can be exploited to tailor the catalyst to less reactive substrates [4] . The products of this reaction are symmetrical bisindolylmethanes that incorporate two identical indole units.…”
Section: Figurementioning
confidence: 99%
“…Recently we reported that trityl cations are exceptional catalysts for the synthesis of bisindolylmethanes via aldehyde activation (Figure 1), and the tunability of these catalysts can be exploited to tailor the catalyst to less reactive substrates [4] . The products of this reaction are symmetrical bisindolylmethanes that incorporate two identical indole units.…”
Section: Figurementioning
confidence: 99%